Segurança jurídica das decisões e o requisito da repercussão geral no recurso extraordinário em matéria tributária - Taleires, Janaina Sena (2013)
Legal Certainty, perceived as an intrinsic element of Justice, aims to avoid the indiscretional will and to ensure equality and isonomy. It is indispensable that Legal Certainty is observed in the context of constitutional matter’s general repercussion. As a legal requirement for the admission of the Extraordinary Appeal, general repercussion acts as a filtering mechanism, selecting the appeals that will be judged by the Supreme Court. The present study objectifies to analise the aspects of general repercussion under the jurisdictional protection of fundamental rights, notedly in what concerns Tax Law, considering the importance of its preservation. It is important to point out that general repercussion´s study needs to be deepened because of its relevance, since Brazil is what can be called a Tax Estate. Said that, it will be analised the conduct of the Supreme Court in the decisions about general repercussion of the Extraordinary Appeals that concern taxing issues, observing the recognition of the transcendence of the objects in discussion, confronting it with the principle of judicial decisions’ legal certainty. In order to achieve that goal, it was indispensable reviewing jurisprudence and using bibliographic researching method. As a result, it was possible to conclude that, in order do minimize the state of legal uncertainty seen nowadays because of oscillating jurisprudences, it is necessary the presumption of general repercussion in taxing matters.